Internet and Network Economics 5th International Workshop, WINE 2009, Rome, Italy, December 14-18, 2009, Proceedings - Leonardi, Stefano (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This book constitutes the refereed proceedings of the 5th International Workshop on Internet and Network Economics, WINE 2009, held in Rome, Italy, in December 2009. The 34 regular and 29 short revised full papers presented together with 3 invited talks were carefully reviewed and selected from 142 submissions. The papers address various topics in theoretical computer science, networking and security, economics, mathematics, sociology, and management sciences devoted to the analysis of problems arising in the internet and the worldwide Web, such as auction algorithms, computational advertising, general and majority equilibrium, coalitions, collective action, economics aspects of security and privacy in distributed and network computing, algorithmic design and game theory, information economics, network games, price dynamics, and social networks.